Purificação e caracterização de uma gentioexaose obtida de botriosferana por hidrólise ácida parcial - Silva, Iara Ribeiro [UNESP]; Monteiro, Nilson Kobori [UNESP]; Martinez, Paula Felippe [UNESP]; Izeli, Nataly Lino [UNESP]; Vasconcelos, Ana Flora Dalberto [UNESP]; Cardoso, Marilsa de Stefani [UNESP]; Silva, Maria de Lourdes Corradi da [UNESP]; Barbosa, Aneli de Melo; Dekker, Robert F. H.; Silva, Gil Valdo José da; Moraes, Luís Alberto Beraldo de (Sociedade Brasileira de Química, 2008)
A hexa-oligosaccharide was obtained by partial acid hydrolysis from botryosphaeran, an exopolysaccharide (EPS) β(1→3; 1→6)-D-glucan type, produced by the ascomyceteous fungus Botryosphaeria rhodina. The oligosaccharide was purified by gel filtration and charcoal-Celite column chromatography and the analysis was followed by HPAEC/PAD. The structure was determined by NMR spectroscopy and mass spectrometry, which showed that the oligosaccharide consists of six β-D-glucopiranosyl units O-6 substituted (gentiohexaose).
Purification and characterization of a gentiohexaose obtained from botryosphaeran by partial acid hydrolysis
Keywords: oligosaccharide; partial acid hydrolysis; β-glucan